EFFECTIVITY METHOD OF CHROMATOGRAPHY TO ISOLATE COMPOUND OF A METABOLITE SECUNDER AT PEPEROMIA PELLUCIDA L. PLANT WITH METHANOL SOLVENT - Lutfiana Kartika Dewi; Muhammad Ghufron; Ngain Kristin (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The aim of this research to identify the efectivity method of chromatography to isolatecompound of a metabolite secunder at Peperomia Pellucida L. plant With methanol solvent. As much as 200 gram simplisia plant macerated with the methanol solvent, n- hexan, and Ethyl acetate during 2x24 hours. Maserat obtained subsequently in distillation to produce condensed of methanol extracts of 40 grams. Extracts of condensed methanol subsequently analyzed using thin layer chromatography to see the existence of compounds in a sample.Results of chromatography thin retrieved the reflection of colors that indicate in plantsecondary metabolite compounds there are messengers.Keywords: Peperomia pellucida L., Isolation, Simplisia, Secondary Metabolites.